2012
DOI: 10.1111/j.1755-3768.2011.02335.x
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed correlation between arterial resistance and pulsatility in glaucoma patients

Abstract: ABSTRACT.Purpose: (i) To investigate whether pulsatility index (PI) and mean flow velocities (MFV) are altered in glaucoma patients. (ii) To evaluate the significance of PI in retrobulbar autoregulation capacity. Methods:Patients with primary open-angle glaucoma (POAG; n = 49), normal tension glaucoma (NTG; n = 62) and healthy controls (n = 48) underwent colour Doppler imaging measurements of the retrobulbar vasculature. Kruskal-Wallis test was used to compare variables between the three diagnostic groups. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…This is important given that contrast sensitivity decreases after menopause, improves after HRT and is affected by normal cycling oestrogen. Coupled with evidence that reduced retinal blood flow may act as a precipitant in the development of glaucoma and AMD (Harris et al 1999, Flammer et al 2002, Pinto et al 2012, these findings support the idea that post-menopausal oestrogen deficiency may, at least circuitously, dispose older females to these age-related ocular diseases.…”
Section: Potential Mechanisms Of Oestrogen Cell Protectionsupporting
confidence: 59%
“…This is important given that contrast sensitivity decreases after menopause, improves after HRT and is affected by normal cycling oestrogen. Coupled with evidence that reduced retinal blood flow may act as a precipitant in the development of glaucoma and AMD (Harris et al 1999, Flammer et al 2002, Pinto et al 2012, these findings support the idea that post-menopausal oestrogen deficiency may, at least circuitously, dispose older females to these age-related ocular diseases.…”
Section: Potential Mechanisms Of Oestrogen Cell Protectionsupporting
confidence: 59%
“…Similarly, a newly published prospective study by Adeyinka et al measured retrobulbar blood flow velocities in African patients with OAG in Nigeria and found reduced peak systolic and end diastolic velocities and increased resistivity in the ophthalmic and central retinal arteries of OAG patients compared to controls (Adeyinka et al 2013). Previous studies have demonstrated a reduction in blood flow velocities in the retrobulbar vessels of glaucoma patients in general (Sergott et al 1994; Nicolela et al 1996; Chiou et al 1999; Akarsu and Bilgili 2004; Abegão Pinto L et al 2012), and lower retrobulbar blood flow within in OAG patients of AD may be a mechanism which contributes to their OAG disease disparity. Importantly, vascular resistance of retrobulbar vessels has been shown to predict visual field progression (Martinez et al 2005); similarly, constricted blood flow has been associated with visual field loss (Galassi et al 2003).…”
Section: Ocular (Localized) Vascular Deficiencymentioning
confidence: 91%
“…70-72 However, the interaction of these vascular systems may play an important role in keeping the ONH healthy. 70 In the early 1970s, contrary results were reported in the regulatory behavior of ChBF during experimental manipulation of ocular perfusion pressure (OPP).…”
Section: Choroidal Blood Flowmentioning
confidence: 99%